Mechanical and Post-Cracking Performance of Recycled Aggregate Concrete Incorporating Synthetic Fibers. Issue 1 (April 2020) - Kazmi, Syed M S; Munir, Muhammad J; Wu, Yufei; Patnaikuni, Indubhushan
Abstract: Reuse of concrete waste in novel construction is becoming very important topic nowadays. This study focuses to examine the post-cracking and mechanical performance, fracture behavior, and micro-structure of fiber strengthened recycled aggregate concrete (RAC). For this purpose, crack mouth opening diameter (CMOD) tests were conducted on twenty-seven notched beam specimens (550 × 150 × 150 mm) having three replacement levels (i.e., 0, 50 and 100%) of recycled concrete aggregates (RCA) and three synthetic fiber dosages (i.e., 0, 0.5 and 1%). Different mechanical properties of all mixes were also examined following ASTM standards. Drop in the mechanical performance of RAC was noticed at higher RCA replacement levels. However, synthetic fiber reinforced RAC showed better performance as compared to plain RAC. Results also depict positive influence of synthetic fiber addition on the residual flexural tensile strength of concrete. Approximately, 129% and 380% rise in toughness index and fracture energy was also observed for 1% fiber incorporation in RAC. Moreover, scanning electron microscopic analysis also confirmed the synthetic fiber-mortar bond. Therefore, synthetic fibers enhance the post-cracking and mechanical performance of fiber reinforced RAC resulting into more ductile and energy absorbing sustainable concrete.